The Level of Moral Thinking of Gifted Students and its Relation With Some Variables in a Jordanian Sample - Awni A. Shahean; Sameer A. Al Reamawi (Journal of Educational and Psychological Studies, 2017)
The current study aimed at identifying the level of moral thinking of gifted students in line with Kohlberg aspects. To achieve the study objectives the moral thinking scale was administered a sample of (115) male and female students from king Abdullah II gifted school in Zarqa city. Another sample of (118) normal male and female students in the same classes were included. The results indicated that the moral level of the sample was in the fourth Kohlberg level. No significant differences among gifted students were found due to gender. There were significant differences among gifted student due to class in favor of higher classes. However, there was no significant difference between gifted and normal students in the level of moral thinking. Students who came from families with great number of siblings outscored students who came from families with small number of siblings. Student order of birth had no significant effect on moral thinking. The researchers proposed recommendations based on the results